PERBEDAAN KETERAMPILAN BELAJAR SISWA BERPRESTASI TINGGI DAN BERPRESTASI RENDAH SERTA IMPLIKASINYA DALAM BIMBINGAN DAN KONSELING - Folastri, Sisca (Konselor, 2013)
The purpose of this research are to describe and distinguishing student’s learning skills achievement of high and low achievement. The research used quantitative approach using comparative descriptive type. The research conducted on students SMA Padang city that accredited A, B, and C in education 2011/2012 with population are 658 students. Number of research samples as much 120 students and in sampling using purposive sampling technique. The findings of this research revealed that (1) are generally high-achieving students 'skills in both categories, (2) skills of underachieving students in both categories, (3) analysis of t test results revealed there were differences in high-achieving students' learning skills and learning skills of students underachieving high schools in the city of Padang. Counselor are expected to help improve learning skills by providing guidance and counseling services to suit the needs of students, for consideration BK programming services in maintaining, developing and improving students' learning skills.